2002
DOI: 10.1016/s0925-4439(01)00107-7
|View full text |Cite
|
Sign up to set email alerts
|

γ-Carboxyglutamic acid content of hepatocellular carcinoma-associated des-γ-carboxy prothrombin

Abstract: Serum des-gamma-carboxy prothrombin (DCP) is a useful marker for the diagnosis of hepatocellular carcinoma (HCC), but the exact mechanism of its synthesis and its structural properties in liver diseases are unknown. DCP is measured by the monoclonal antibody MU-3. The purpose of this study was to examine the epitope of MU-3 and to characterize the differences in DCP between HCC and benign liver diseases. The epitope of MU-3 was examined by ELISA using prothrombin Gla domain polypeptides and was determined to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…These Gla residues are originally glutamic acid (Glu) residues in prothrombin precursor. The ten Glu residues are respectively at the positions of 6, 7, 14, 16, 19, 20, 25, 26, 29, and 32 in N-terminal domain [1,12]. In hepatocyte, these Glu residues must be converted into Gla residues before prothrombin obtains the coagulation activity.…”
Section: The Structure Of Dcpmentioning
confidence: 99%
See 1 more Smart Citation
“…These Gla residues are originally glutamic acid (Glu) residues in prothrombin precursor. The ten Glu residues are respectively at the positions of 6, 7, 14, 16, 19, 20, 25, 26, 29, and 32 in N-terminal domain [1,12]. In hepatocyte, these Glu residues must be converted into Gla residues before prothrombin obtains the coagulation activity.…”
Section: The Structure Of Dcpmentioning
confidence: 99%
“…DCP lacks the activity of interacting with other coagulation factors [1,2]. Since Liebman et al reported an elevated plasma DCP in patients with HCC, DCP has been considered as a specific marker for diagnosis of HCC [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…DCP is an abnormal prothrombin that is produced by under-carboxylation of normal prothrombin [37] . Suzuki et al [38] reported that DCP exerts a mitogenic effect on hepatocellular carcinoma cells via a Met-Janus kinase 1-STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the precise mechanism underlying DCP production is still controversial. Prothrombin is synthesized in the liver depending on the presence of vitamin K-dependent ␥ -glutamyl carboxylase in the posttranslational process [4][5][6]20] . The prothrombin precursor has 10 Glu residues in the N-terminus that are converted into ␥ -carboxy-glutamic acid (Gla) residues by ␥ -glutamyl carboxylase in the presence of vitamin K [21] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that recurrence and metastasis are more frequent in HCC patients with positive des-␥ -carboxy prothrombin (DCP) than in patients with negative DCP [2][3][4] . DCP (also known as protein induced by vitamin K absence or antagonist-II) is an abnormal prothrombin that is not completely carboxylated by the shortage of vitamin K [5] . Recently, DCP has been reported as a potential autologous growth factor for HCC development.…”
Section: Introductionmentioning
confidence: 99%